Solusi Teknologi SIMRS dalam Meningkatkan Kualitas Layanan Kesehatan Publik di Indonesia - Dina Hartati Rambe; Mariani Lubis; Nursia Ritonga; Sri Hajijah Purba (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2025)
The implementation of the Hospital Information Management System (SIMRS) plays a crucial role in enhancing the quality of public healthcare services in Indonesia. With the country's vast geographical landscape and significant disparities in healthcare access between urban and rural areas, SIMRS offers an integrated digital solution to streamline hospital operations and improve service delivery. This study explores the impact of SIMRS on the efficiency of hospital management, particularly in administrative processes such as patient registration, medical records, and resource allocation. Additionally, SIMRS contributes to improving healthcare accessibility by enabling seamless data exchange between healthcare facilities, ensuring that patients in remote areas can access timely and appropriate care. Despite its benefits, the implementation of SIMRS faces challenges, such as limited infrastructure, high implementation costs, and a lack of trained personnel. To overcome these obstacles, it is essential for the government, healthcare institutions, and other stakeholders to collaborate in providing adequate training, improving infrastructure, and ensuring sustainable implementation of SIMRS. This study concludes that SIMRS has the potential to significantly improve healthcare services in Indonesia, provided that the challenges are addressed and adequate support is given for its expansion across the country.